RETRACTED: In vitro BSA-binding, antimicrobial, and antitumor activity against human cancer cell lines of two lanthanide (III) complexes - Obaid, Rasha Fadhel; Alsaikhan, Fahad; Tizkam, Hussam H.; Alamir, Hassan Thoulfikar A.; Jandari Jumaa, Hamad; Waleed, Ibrahem; Ahmad, Irfan; Shnain Ali, Mohammed; Asiri, Mohmmed (Frontiers in Chemistry, 2023)
The investigation involved examining the binding of two lanthanide complexes, specifically those containing Holmium (Ho) and Dysprosium (Dy), with a ligand called 1, 10-phenanthroline (phen), and bovine serum albumin (BSA). The evaluation was carried out utilizing fluorescence measurements, Förster theory, and docking studies. The findings indicated that both the Ho-complex and Dy-complex possessed a significant ability to quench the emission of the protein. Furthermore, the primary mechanism of interaction was identified as a static process. The Kb values indicate a strong tendency of these complexes for binding with BSA. The Kb values show the strangely high affinity of BSA to complexes and the following order for binding affinity: Ho-complex > Dy-complex. The thermodynamic parameters were found to be negative, affirming that the main forces driving the interaction between BSA and the lanthanide complexes are van der Waals engagement and hydrogen bonds. Additionally, the investigation included the examination of competition site markers, and molecular docking proposed that the engagement sites of the Ho-complex and Dy-complex with BSA were predominantly located in site 3 (specifically, subdomain IB). Moreover, the Ho-complex and Dy-complex were specifically chosen for their potential anticancer and antimicrobial properties. Consequently, these complexes could present promising prospects as novel candidates for anti-tumor and antibacterial applications.